Succession to Power and the Principles of Availability and Immediacy. From Medieval France to the Contemporary Latin American Vice Presidency (Res Publica. Revista de Historia de las Ideas Políticas, 2021)
Many elements of our political systems have a theoretical foundation, a profound study of the theoretical and practical principles that explain their adoption. On the contrary, the vice presidency has received very little attention, even in countries where this institution has been gaining remarkable political weight. The combination of this weight with the aforementioned lack of theoretical support produces notable deviations in the analyses of the institution and its performance — they try to study the fruit without knowing the roots. The aim of this article is to carry out a first theoretical reflection in this field, analysing the vice presidency in presidential systems in light of two theoretical principles — immediacy and availability of power.